(3QSGdI GdUMHI GdcGFfIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3QSGdI ef gGOi GdeSJLjHjf GdefJbe ef GdeTQcjf HSja ehdGfG SHMGfg Edi CUMGH JTcjf GdeYJbdjf s
(3BNQgG (B:s
(3hEf cGf eG jNai YfgG TF ef CMhGdce hGdMeO dehdGfG hMOg ai GdSQGA hGdVQGA hGdTOI hGdQLGA hgh MSHi hfYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B20s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds